Ecological nutrient solutions on yield and quality of melon fruits - Gonzalez, Jose Antonio; García-Villela, Karen Marlen; Preciado-Rangel, Pablo; Sifuentes-Ibarra, Ernesto; Salas-Pérez, Lilia; Núñez-Ramírez, Fidel (REVISTA TERRA LATINOAMERICANA, 2020)
Due to health benef its, organic food products have increased their demand in recent years. The objective was evaluating the effects of three ecological nutrient solutions, (Tea of compost, vermicompost, and leachate of vermicompost), on yield and quality of melon plants. As a control, an inorganic nutrient solution was used. Our results showed that compost tea promoted fruit yield equivalent to the inorganic nutrient solution. Plants fertilized with compost tea yielded fruits with the highest value of soluble solids content (9.98 ºBrix). Regarding antioxidant capacity, fruits fed with compost tea and vermicompost leachate obtained higher values than fruits fed with nutrient solution, fruits fed with vermicompost leachate obtained statistically higher values than fruits fed with chemical nutrient solution. Concerning to total phenolic content plants fed with vermicompost leachate obtained the highest value statistically similar to control plants fed with the Steiner nutrient solution.